Are boys and girls affected differently when the household head leaves for good? Evidence from school and work choices in Colombia - Emla Fitzsimons; Alice Mesnard (Institute for Fiscal Studies (IFS), 2008)
This paper investigates how the permanent departure of the head from the household, mainly due to death or divorce, affects children's school enrolment and work participation in rural Colombia. In our empirical specification we use household-level fixed effects to deal with the fact that households that experience the departure of the head are likely to differ in unobserved ways from those that do not, and we also address the issue of non-random attrition from the panel. We find remarkably different effects for boys and girls. For boys, the adverse event reduces school participation and increases participation in paid work, whereas for girls we find evidence of the adverse event having a beneficial impact on schooling. To explain these differences, we provide evidence for boys consistent with the head's departure having an important effect through the income reduction associated with it, whereas for girls, changes in the household decision-maker appear to play an important role.
Keywords: I20; J12; J22; O16; 330; Child labour; Schooling; Adverse event; Income loss; Credit and insurance market failures; Bargaining; Familie; Eltern; Scheidung; Unfall; Kinder; Geschlecht; Schulauswahl; Erwerbstätigkeit; Kolumbien